Sungkai Leaf Extract (Peronema canescens Jack) Reduces MDA Levels and Increases IL-10 Levels in MSG-Induced Wistar Rats - Wahyudi, Wahyudi; Chodijah, Chodijah; Sumarawati, Titiek; Afrianti, Dina (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The addition of Monosodium Glutamate (MSG) to ready-to-eat food can change eating habits, coupled with a lack of activity which can have an impact on health. MSG as a trigger for increased reactive oxygen species (ROS), causing systemic damage, the impact of excessive MSG consumption can be reduced by modifying the diet to contain high sources of antioxidants. Sungkai leaf extract can be an alternative as a natural antioxidant. Sungkai leaf extract antioxidants are expected to neutralize ROS thereby repairing cell damage. Objective: This study aims to determine how giving sungkai leaf extract affects MDA and IL-10 levels in MSG-induced mice. Method: Experimental research with a Randomized Post test only control group design. The total sample was 24 male Wistar rats divided into 4 groups. KN healthy mice, K(-) were given 1g MSG/rat, P1 was given 1g MSG/rat and 28mg sungkai leaf extract/rat, P2 was given 1g MSG/rat and 56mg sungkai leaf extract/rat. Results: The average results showed a decrease in MDA levels and an increase in IL-10 levels after treatment for 21 days, the One way Anova test followed by Post hoc LSD showed that each treatment group was significantly different from the control group where the MDA level in group P2 was 0, 07mg/ml ± 0.01 experienced a significant decrease compared to the KN group 0.07mg/ml ± 0.01 while IL-10 levels experienced a significant increase in the P1 group 130.10pg/ml ± 13.29 when compared to the KN group 60.43pg/ml ±17.40. Conclusion: Sungkai leaf extract (Penonema Canescens Jack) was able to reduce MDA levels at a dose of 56 mg/mouse in mice injected with 1gr MSG/rat and experienced a significant increase in IL-10 levels with a dose of 28 mg sungkai leaf extract/rat injected with 1gr MSG/rat.